2001
DOI: 10.1179/016164101101198532
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation and acoustic trauma or hearing loss in children

Abstract: Transcranial magnetic stimulation is a non-invasive method used to assess motor function in humans; however, some reports suggest it may cause internal ear damage (cochlear). Eighteen patients with normal auditory function (ages 2 months to 16 years, mean 6.8 years), two medical doctors and two technicians who performed the studies were tested with brain stem auditory evoked potentials, otoacoustic emissions, acoustic reflex and a pure tone audiometric and logoaudiometric test when possible, before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Furthermore, when observed, transitory neurophysiological changes were not associated with a significant increase in spike-wave discharges in a population of brain-damaged children (Gilbert et al, 2004 ). rTMS was not found to be associated with cochlear damage or hearing-loss in children or adolescents who received neurostimulation treatment (Collado-Corona et al, 2001 ). Finally, using a self-report acceptability questionnaire, Garvey et al ( 2001 ) found that for 38 children and adolescents receiving this treatment, the TMS tolerability ranged between a long drive and an appointment to the dentist.…”
Section: Acceptability Issuesmentioning
confidence: 99%
“…Furthermore, when observed, transitory neurophysiological changes were not associated with a significant increase in spike-wave discharges in a population of brain-damaged children (Gilbert et al, 2004 ). rTMS was not found to be associated with cochlear damage or hearing-loss in children or adolescents who received neurostimulation treatment (Collado-Corona et al, 2001 ). Finally, using a self-report acceptability questionnaire, Garvey et al ( 2001 ) found that for 38 children and adolescents receiving this treatment, the TMS tolerability ranged between a long drive and an appointment to the dentist.…”
Section: Acceptability Issuesmentioning
confidence: 99%
“…In addition, a study of 18 children ranging from 2 months to 16 years of age reported formal testing of brainstem auditory evoked potentials, otoacoustic emissions, acoustic reflex and pure tone audiometric tests performed before and after TMS with no hearing protection. No abnormalities of hearing function were found [30]. Based on these human studies and complimentary animal data, current single and paired pulse protocols do not appear to pose a hearing risk.…”
Section: Safety and Tolerability Of Tms In Childrenmentioning
confidence: 99%
“…In a TMS study with a typical diagnostic testing time and TMS exposure (a median of 19 TMS pulses at a median stimulation intensity of 68% maximum stimulator output), Collado-Corona and colleagues reported no significant change in pure tone thresholds in a group of 18 children without hearing protection (18). In another study designed to inform investigators and Institutional Review Boards on the safety of TMS use in children, the theoretical risk to hearing was analyzed and described to be minimal based on comparing the level of noise from a TMS pulse, its frequency, and exposure time to standards set by the National Institute for Occupational Safety and Health (3).…”
mentioning
confidence: 99%
“…TMS was conducted for the purposes of a pathophysiological investigation of cortical excitability in individuals with childhood-onset motor disabilities, not relevant for the current analysis. We exposed participants to a longer TMS session with more stimuli than previously reported (18). Participants used hearing protection as advised (12, 16), allowing assessment of the effects of standard TMS protocols on hearing.…”
mentioning
confidence: 99%